AESTHETIC ANALYSIS OF CARVING THE ATMOSPHERE OF RURAL MARKETS IN THE MIDST OF THE DEGRADATION OF YOUTH INTEREST IN SENENAN VILLAGE - Amelia Lysanties; Wasis Wijayanto (Eduarts: Jurnal Pendidikan Seni, 2025)
Jepara is known as the "City of Carving" and has been globally recognized since the 1990s. The people of Jepara primarily work as carving artisans, which is a local cultural identity that is globally competitive. This research is a case study type of research with a qualitative approach. The data collection techniques used are: observation, interviews, and documentation to gather data regarding the "Rural Market Atmosphere" carving. Observation was conducted at the location of the Yohanes Shefta Adinata carving art gallery, Senenan Village, RT.04 RW.02 on October 2, 2025. The interview was conducted by asking questions to Yohannes as the resource person. Meanwhile, documentation was done by taking photos with the resource person as support for the research. Data analysis techniques are carried out thru data reduction, data presentation, data verification, or drawing conclusions. The research results show: (1) The process of making wood carvings starts from the preparation stage, thru the creation stage, and ends with the finishing stage. (2) The aesthetic elements of lines, shapes, texture, space, color, and light and shadow are present in the wood carving "Rural Market Atmosphere". (3) There is interest among the younger generation in wood carving in Senenan village. The purpose of this research is to understand the wood carving process, identify the aesthetic elements in the "Rural Market Atmosphere" carving, and understand the interest of the younger generation in wood carving in Senenan village.